DESKRIPSI KEMAMPUAN MULTIREPRESENTASI PADA MATERI LAJU REAKSI SISWA KELAS XI IPA SMA MUHAMMADIYAH 1 KETAPANG - Widi Wahyudi; Mahwar Qurbaniah; Rody Putra Sartika (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to describe the symbolic, the microscopic, and the macroscopic levels of multi representation skills on Reaction Rate class among Science students of the eleventh grade of SMA Muhammadiyah Ketapang. The subjects of this study were 30 eleventh grade Science students of SMA Muhammadiyah ketapang. The data collection techniques were interview and test. The study reveals a number of findings. First, the symbolic level of multi representation skills of the first question was 86,5% (excellent), the second question was 59,22% (average), and the third question was 66% ( good). In other words, the students’ skill on symbolic level of multi representation is considered good by 70,57%. Second, the students’ skill on macroscopic level of multi representation on question number four is considered excellent by 83,86%, question number five is considered average by 68,57%, and question number six is considered very good by 77,14%. Overall, the students’ skill on macroscopic level of multi representation is very good by 76,52%. Last, the students’ skill on microscopic level of multi representation on question number seven is considered average by 52,86%, question number eight is considered poor by 36,14%, and question number nine is considered poor by 34,71%. In conclusion, the students’ skill on microscopic level of multi representation is below average by 41,25%.Keywords: Description, Multi Representation Skills, Reaction Rate